Assessing the influence of neglected GC-FID variables on the multiple responses using multivariate optimization for the determination of ethanol and acetonitrile in radiopharmaceuticals - Hassan, Hishar; Othman, Muhammad Faiz; Zakaria, Zainul Amiruddin; Ahmad Saad, Fathinul Fikri; Abdul Razak, Hairil Rashmizal (Springer, 2021)
Analytical gas chromatography in line with a flame ionization detector (GC-FID) method was developed and validated for direct determination of organic solvents in [18F]fluoro-ethyl-tyrosine ([18F]FET), [18F]fluoromisonidazole ([18F]FMISO) and [18F]fluorothymidine ([18F]FLT). Variables of the splitless time (min) and injection temperature (°C) on the response of analysis time and resolution were optimized with the assistance of a two-level full factorial design and desirability function of Derringer. The proposed procedure was validated following the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) Q2 (R1) guideline. Excellent linearity, R2 > 0.990, indicated that approximately 99% of the response variance could be predicted from ethanol and acetonitrile concentrations ranging from 0.5 to 6.0 mg mL−1 and 0.1 to 0.8 mg mL−1, respectively. The proposed procedure has proved to be selective, sensitive, and accurate (90–110%), with excellent repeatability and precision (RSD < 2%). In the robustness analysis, the findings from the calculated Standardized Effects Values (SE) were insignificant (p > 0.05) and demonstrated that the proposed method was robust for a splitless time of 1.0 ± 0.5 min and an injection temperature of 210 ± 10 °C. The proposed method was also successfully used for the quantitative determination of ethanol and acetonitrile in [18F]FET, [18F]FMISO, and [18F]FLT. Both solvents were well separated (R, 4.1–4.3) within 4.5 min. Therefore, the proposed method is relevant for routine quality control analysis of all 18F-radiopharmaceutical derivatives for the direct determination of ethanol and acetonitrile.